2008
DOI: 10.1111/j.1872-034x.2007.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genipin on the biliary excretion of cholephilic compounds in rats

Abstract: It was indicated that colchicine-sensitive vesicular transport has no role on the genipin-induced insertion of Mrp2 to the canalicular membrane. Choleresis of genipin is considered to be mainly due to the increased biliary glutathione excretion by genipin, not by the biliary excretion of glucuronide. TC had no effect on the biliary glutathione excretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“… 11,12 reported that genipin stimulated the insertion of the multidrug resistance protein 2 (Mrp2) into the bile canalicular membrane, thereby causing choleresis by increasing the biliary excretion of glutathione, which has been considered to be a substrate of Mrp2. We also confirmed that genipin caused choleresis by increasing biliary glutathione excretion 13 . Recent studies have shown that genipin exhibits protective effects in mouse neuroblastoma cells, 14,15 and inhibits exocytosis in human endotherial cells 16 …”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“… 11,12 reported that genipin stimulated the insertion of the multidrug resistance protein 2 (Mrp2) into the bile canalicular membrane, thereby causing choleresis by increasing the biliary excretion of glutathione, which has been considered to be a substrate of Mrp2. We also confirmed that genipin caused choleresis by increasing biliary glutathione excretion 13 . Recent studies have shown that genipin exhibits protective effects in mouse neuroblastoma cells, 14,15 and inhibits exocytosis in human endotherial cells 16 …”
Section: Introductionsupporting
confidence: 79%
“…Thirty minutes after bile duct cannulation, a tracer dose of [ 3 H]VLB (5.9 × 10 5 dpm) was injected via the femoral vein, and genipin was infused at the rate of 0.5 µmol/min/100 g for 90 min 13 . Bile samples were collected every 10 min, and the radioactivity was counted.…”
Section: Methodsmentioning
confidence: 99%
“…28 However, since the dose of pravastatin used in the present study was that to cause its biliary excretory maximum in order to examine whether pravastatin inhibits biliary bile acid excretion. 12,21 Therefore, it is quite unlikely that pravastatin significantly inhibits biliary bile acid excretion by its therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty min after bile duct cannulation, [ 14 C] pravastatin was infused into SD rats at the rate of 0.3 µmol/min/100 g for 90 min, which causes the excretory maximum of pravastatin in rats 12,21 . TC or TUDC was simultaneously infused at the rate of 1 µmol/min/100 g, and the radioactivity of the bile samples every 10 min was counted by a liquid scintillation counter.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In addition, genipin, which is the aglycone portion of geniposide and is formed as a metabolite, is also reported to have an anti-inflammatory effect, a bile secretion-enhancing effect, and an anti-thrombotic effect. [10][11][12] Geniposide is promising as a seed compound for developing therapeutic medicines for metabolic diseases. However, no publication has reported the effect of geniposide on various metabolic disease symptoms based on visceral fat accumulation.…”
mentioning
confidence: 99%